Gut microbiota: a potential new regulator of hypertension - Ge, Yanmin; Wang, Jiaxin; Wu, Lincong; Wu, Junduo (Frontiers in Cardiovascular Medicine, 2024)
Hypertension is a significant risk factor for cardiovascular and cerebrovascular diseases and has become a global public health concern. Although hypertension results from a combination of factors, the specific mechanism is still unclear. However, increasing evidence suggests that gut microbiota is closely associated with the development of hypertension. We provide a summary of the composition and physiological role of gut microbiota. We then delve into the mechanism of gut microbiota and its metabolites involved in the occurrence and development of hypertension. Finally, we review various regimens for better-controlling hypertension from the diet, exercise, drugs, antibiotics, probiotics, and fecal transplantation perspectives.